Effect of fine modulus of coarse aggregate on the mechanical properties of concrete submerged in sea water - Sulkarnain, Sulkarnain; Erniati, Erniati; Gusty, Sri; Ritnawaty, Ritnawaty; Ashraf, Ashraf; Huda, Miftakhul; Putri, Herwina Rahayu (ASTONJADRO, 2024)
The durability of concrete can be determined from mixing coarse aggregate, fine aggregate, cement, water, with or without additives. The properties of concrete can be influenced by several things, such as the ratio of the mix, how to mix, how to transport, how to print, and how to compact. To analyze the compressive strength, flexural strength and split tensile strength of concrete submerged in sea water with variations in fineness modulus. The compressive strength results were 35.67Mpa, 31.63Mpa, 29.30Mpa respectively while the compressive strength of concrete with seawater immersion was 36.94Mpa, 36.52Mpa and 30.15Mpa. The split tensile strength results were 2.71Mpa, 2.65Mpa and 1.91MPa respectively, while the split tensile strength of concrete immersing in seawater with the same variations were 3.29MPa, 2.76MPa and 2.12MPa, respectively. The results of flexural strength were 4.22Mpa, 4.21Mpa, and 4.14MPa respectively, while the flexural strength of concrete with seawater immersion with the same variations were 4.27MPa, 4.22MPa, and 4.18MPa, respectively. The effect of fine grain modulus on compressive strength, split tensile strength and resulting flexural strength is very significant, the higher the fineness modulus of the coarse aggregate, the smaller the resulting value.